A Call to Expand Avian Vocal Development Research - Loo, Yen Yi; Cain, Kristal E. (Frontiers in Ecology and Evolution, 2021)
Birds are our best models to understand vocal learning - a vocal production ability guided by auditory feedback, which includes human language. Among all vocal learners, songbirds have the most diverse life histories, and some aspects of their vocal learning ability are well-known, such as the neural substrates and vocal control centres, through vocal development studies. Currently, species are classified as either vocal learners or non-learners, and a key difference between the two is the development period, extended in learners, but short in non-learners. But this clear dichotomy has been challenged by the vocal learning continuum hypothesis. One way to address this challenge is to examine both learners and canonical non-learners and determine whether their vocal development is dichotomous or falls along a continuum. However, when we examined the existing empirical data we found that surprisingly few species have their vocal development periods documented. Furthermore, we identified multiple biases within previous vocal development studies in birds, including an extremely narrow focus on (1) a few model species, (2) oscines, (3) males, and (4) songs. Consequently, these biases may have led to an incomplete and possibly erroneous conclusions regarding the nature of the relationships between vocal development patterns and vocal learning ability. Diversifying vocal development studies to include a broader range of taxa is urgently needed to advance the field of vocal learning and examine how vocal development patterns might inform our understanding of vocal learning.